High-transparency explosion-proof glass and preparation process thereof

By using specific formulas and processes during the glass preparation process, including directional stress and rapid cooling treatment, a hard-soft-hard layered structure is formed, which solves the limitations of traditional glass in terms of explosion-proof and transparency, achieving high transparency and excellent explosion-proof performance.

CN119330590APending Publication Date: 2025-01-21YANGZHOU BAOCHENG SPECIAL GLASS MATERIALS CO LTD

Patent Information

Application Number
CN202411885150.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Traditional glass has limitations in terms of explosion-proof, transparency and impact resistance. The existing explosion-proof glass technology often affects transparency when improving explosion-proof performance, and it is difficult to achieve uniform distribution of stresses inside the glass, resulting in optical distortion or crack propagation.

Method used

A liquid glass matrix is ​​formed by mixing quartz sand, sodium oxide, calcium oxide, boron oxide, potassium carbonate, Glauber's salt, zinc oxide, cesium nitrate and Al2O3 nanoparticles in proportion and performing pretreatment in a molten state. Then, directional stress is applied to the semi-solid glass matrix to control the uniform distribution of Al2O3 nanoparticles, and a hard-soft-hard layered structure is formed through rapid cooling treatment, and finally the surface is chemically strengthened or physically coated.

Benefits of technology

It achieves high transparency and excellent explosion-proof performance. Through the uniformly distributed Al2O3 nanoparticles and network structure, it effectively absorbs and disperses external impacts, avoids stress concentration and crack expansion, and improves the overall performance and safety of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330590A_ABST
    Figure CN119330590A_ABST
Patent Text Reader

Abstract

The invention discloses high-transparency explosion-proof glass and a preparation process thereof, and the preparation process comprises the following steps: uniformly mixing a glass substrate and Al2O3 nanoparticles in proportion, and heating until a molten state to obtain a liquid glass matrix; the method comprises the following steps: introducing a liquid glass matrix into a forming mold, and pre-cooling the liquid glass matrix to enable the liquid glass matrix to be in a semi-solid state; the method comprises the following steps: applying directional stress to a semi-solid glass substrate, and cooling the semi-solid glass substrate to obtain a compression layer, so that the glass is of a hard-soft-hard layered structure; directional stress is applied to the semi-solid glass substrate, so that Al2O3 nanoparticles are uniformly enriched on two surfaces of the glass substrate and are quickly cooled, a compression layer is formed on the surface of the glass, and a relatively small tensile stress layer is formed inside the glass, so that the glass is of a hard-soft-hard layered structure, external force impact can be effectively absorbed and dispersed, and the service life of the glass is prolonged. Stress concentration and crack propagation are avoided, the internal structure of the glass is protected, and the anti-explosion performance and durability of the glass are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass preparation, and in particular to a highly transparent explosion-proof glass and a preparation process thereof. Background Art

[0002] Traditional glass is widely used in the fields of construction, automobile, aviation, etc. due to its unique physical and chemical properties. However, ordinary glass has certain limitations in terms of explosion-proof, transparency and impact resistance. Especially in terms of explosion-proof performance, ordinary glass is prone to break when subjected to impact or explosion pressure, resulting in safety hazards. In terms of transparency, the light transmittance of traditional glass may be limited by its internal stress, impurities or structural inhomogeneity; with the advancement of science and technology and the increase in application needs, high-transparency and excellent explosion-proof glass has gradually become an urgent need in the market. Highly transparent explosion-proof glass not only needs to have excellent light transmittance, but also needs to have better anti-destruction performance when subjected to impact or explosion pressure. This requires that in the preparation process of glass, not only the material formula should be optimized, but also the preparation process should be improved to improve the overall performance of the glass.

[0003] Existing explosion-proof glass technology usually improves the explosion-proof performance of glass through multi-layer composite structure, chemical strengthening or special physical coating. Although these technologies can improve the strength and toughness of glass to a certain extent, they often affect its transparency; in addition, the traditional explosion-proof glass preparation process is difficult to achieve uniform distribution of stress inside the glass, which may lead to optical distortion or crack expansion during use.

[0004] Therefore, it is necessary to design a highly transparent explosion-proof glass and a preparation process to solve the above problems. Summary of the invention

[0005] The present invention overcomes the deficiencies of the prior art and provides a highly transparent explosion-proof glass and a preparation process.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a preparation process of highly transparent explosion-proof glass, comprising the following steps: Step S1, mixing quartz sand, sodium oxide, calcium oxide, boron oxide, potassium carbonate, sodium sulfate, zinc oxide, cesium nitrate, and Al2O3 nanoparticles in proportion and heating until they are molten to obtain a liquid glass matrix; Step S2, introducing the liquid glass matrix into a forming mold, and precooling the liquid glass matrix to make it in a semi-solid state; Step S3, applying directional stress to the semi-solid glass matrix to control the symmetrical and uniform distribution of Al2O3 nanoparticles inside the semi-solid glass matrix, and cooling the semi-solid glass matrix to obtain a compression layer, so that the glass has a hard-soft-hard layered structure; Step S4: performing surface treatment on the formed solid glass, including but not limited to chemical strengthening or physical coating.

[0007] In a preferred embodiment of the present invention, step S1 includes the following sub-steps: Step S11, selecting a glass substrate raw material, mixing 100 parts by weight of quartz sand, 15-20 parts by weight of sodium oxide, 10-15 parts by weight of calcium oxide, 6-18 parts by weight of boron oxide, 5-12 parts by weight of potassium carbonate, 3-7 parts by weight of zinc oxide, and 1-5 parts by weight of cesium nitrate, selecting 1.5-5.5 parts by weight of Al2O3 nanoparticles, modifying the Al2O3 nanoparticles, and mixing with the glass substrate raw material for 20-30 minutes; Step S12, drying the mixed raw materials at 110° C. for 2-3.5 hours to remove moisture from the mixed raw materials, and gradually heating the dried mixed raw materials to 350-550° C. for preheating; Step S13, gradually heating the preheated raw material mixture to 1450-1750° C. and maintaining the temperature for 2.5-6 hours until the raw material mixture is fully melted and forms a uniform glass liquid; Step S14: After melting is completed, 2-8 parts by weight of Glauber's salt is added and stirred, and the glass liquid is maintained at a high temperature of 1450-1750° C. for 0.5-2 hours to ensure thorough clarification and achieve uniform chemical composition, thereby obtaining a liquid glass matrix.

[0008] In a preferred embodiment of the present invention, in step S11, the modification treatment of Al2O3 nanoparticles includes the following steps: Step S111, selecting Li2O as a modifier, mixing Al2O3 nanoparticles and Li2O for 20-30 minutes to ensure that Li2O is evenly distributed on the surface of the Al2O3 nanoparticles; Step S112, heating the uniformly mixed Al2O3 nanoparticles and Li2O to 150-225°C, preheating for 1.5-2h to remove the existing moisture and volatile impurities; Step S113, heating the preheated Al2O3 nanoparticles and Li2O at a high temperature of 850-1000°C for 1.25-2 hours to form a lithium aluminum compound layer covering the surface of the Al2O3 nanoparticles; Step S114, cooling the Al2O3 nanoparticles processed in step S113 to 23-25°C at a speed of 50-100°C / min.

[0009] In a preferred embodiment of the present invention, the mass ratio of Al2O3 nanoparticles to Li2O is 25:1-3.

[0010] In a preferred embodiment of the present invention, in step S2, the pre-cooling treatment is specifically to cool the liquid glass matrix to a semi-solid state in the range of 500-750°C, at which time the glass has a certain fluidity but is no longer completely liquid.

[0011] In a preferred embodiment of the present invention, in step S3, directional stress is applied to the semi-solid glass substrate. Specifically, an electric field is applied to both the upper and lower surfaces of the semi-solid glass substrate, and the electric field strength is set in the range of 10^4-10^6V / m, and the application time is 5-10min.

[0012] In a preferred embodiment of the present invention, in step S3, the temperature is lowered, specifically, after the arrangement of the Al2O3 nanoparticles is completed, the temperature is lowered at a rate of 10-45°C / min to solidify the glass.

[0013] In a preferred embodiment of the present invention, in step S4, surface treatment of the formed solid glass comprises: The formed solid glass is subjected to chemical strengthening treatment by immersing the formed solid glass in a potassium nitrate molten bath at a temperature of 400-475° C. for 1.25-2 hours. After the immersion is completed, the solid glass is cooled to 23-25° C. at a rate of 15-30° C. / min.

[0014] A highly transparent explosion-proof glass is prepared based on the above-mentioned preparation process of the highly transparent explosion-proof glass.

[0015] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention provides a highly transparent explosion-proof glass and a preparation process thereof. Directional stress is applied to a semi-solid glass matrix to uniformly enrich Al2O3 nanoparticles on both sides of the glass matrix. The semi-solid glass matrix is ​​then rapidly cooled to form a compression layer on the glass surface and a relatively small tensile stress layer inside the glass. The glass thus presents a hard-soft-hard layered structure, which can effectively absorb and disperse external force impacts, avoid stress concentration and crack propagation, protect the internal structure of the glass, and improve the explosion-proof performance and durability of the glass.

[0016] (2) The present invention provides a highly transparent explosion-proof glass and a preparation process thereof. Al2O3 nanoparticles are used as reinforcing particles to react with quartz sand and boron oxide to generate a network structure of aluminum borate and aluminum silicate. While improving the explosion-proof performance of the glass, the optical properties of the glass are made more uniform, the refraction and scattering of light are reduced, and the transparency is improved. With the directional stress applied by the electric field, the Al2O3 nanoparticles are evenly dispersed on both sides of the glass matrix and embedded in the network structure, making the structure of the glass compression layer more compact, further improving the explosion-proof performance of the glass compression layer, preventing the generation and expansion of cracks, and helping to reduce the scattering and absorption of light, so that the glass maintains high transparency.

[0017] (3) The present invention prepares the glass into a hard-soft-hard layered structure, so that the glass on both sides of the glass becomes a more compact compression layer. The compression layer can withstand and disperse the stress applied from the outside, thereby reducing the internal stress concentration. The middle soft layer can absorb and disperse the pressure applied from the outside under the action of stress, thereby slowing down the transfer of stress to the compression layer, reducing the propagation and concentration of stress inside the glass, and making the overall stress distribution of the glass more uniform, which not only improves the explosion-proof performance of the glass, but also reduces the optical distortion and crack generation caused by internal stress.

[0018] (4) The present invention effectively fills the tiny gaps and defects in the glass by generating a network structure of aluminum borate and aluminum silicate, which helps to improve the optical consistency of the glass and reduce the optical distortion caused by the uneven internal structure, thereby reducing the scattering and reflection of light and improving the transmittance of light. At the same time, the formed stable network enhances the overall structural stability of the glass.

[0019] (5) In the present invention, the Al2O3 nanoparticles are evenly distributed in the glass matrix, which effectively reduces the generation of bubbles and avoids the scattering of light, thereby improving transparency. At the same time, the even distribution of the Al2O3 nanoparticles helps to disperse stress, reduce optical distortion caused by internal stress, and further improve the transparency of the glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 The present invention is a process flow chart for preparing a highly transparent explosion-proof glass. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0023] like Figure 1 As shown, a preparation process of highly transparent explosion-proof glass comprises the following steps: Step S1, mixing quartz sand, sodium oxide, calcium oxide, boron oxide, potassium carbonate, sodium sulfate, zinc oxide, cesium nitrate, and Al2O3 nanoparticles in proportion and heating until they are molten to obtain a liquid glass matrix; In the step S1, the following sub-steps are included: Step S11, selecting a glass substrate raw material, which is 100 parts by weight of quartz sand, 15-20 parts by weight of sodium oxide, 10-15 parts by weight of calcium oxide, 6-18 parts by weight of boron oxide, 5-12 parts by weight of potassium carbonate, 3-7 parts by weight of zinc oxide, and 1-5 parts by weight of cesium nitrate, selecting 1.5-5.5 parts by weight of Al2O3 nanoparticles, and modifying the Al2O3 nanoparticles to improve the dispersibility of the Al2O3 nanoparticles and the reaction activity with the glass substrate, and mixing and stirring with the glass substrate raw material for 20-30 minutes, so that the glass substrate raw material and the Al2O3 nanoparticles are evenly mixed; Step S12, drying the mixed raw materials at 110° C. for 2-3.5 hours to remove moisture from the mixed raw materials, ensuring that the surface of the nanoparticles is clean, which is conducive to subsequent reactions, and gradually heating the dried mixed raw materials to 350-550° C. for preheating; Step S13, gradually heating the preheated raw material mixture to 1450-1750° C. and maintaining the temperature for 2.5-6 hours, and melting the raw material mixture at high temperature to ensure that the components in the glass liquid are completely fused and avoid component segregation, thereby obtaining a glass matrix with uniform chemical composition and no defects; Step S14, after melting is completed, 2-8 parts by weight of Glauber's salt is added and stirred, and the glass liquid is maintained at a high temperature of 1450-1750° C. for 0.5-2 hours to ensure thorough clarification and achieve uniform chemical composition, thereby obtaining a liquid glass matrix; Among them, Al2O3 nanoparticles with a particle size of 10-25nm are added to the glass matrix as reinforcement particles. Al2O3 nanoparticles react with quartz sand and boron oxide under high temperature environment to form a network structure of aluminum borate and aluminum silicate, which can not only improve the explosion-proof performance of the glass, but also make the optical properties of the glass more uniform, reduce the refraction and scattering of light, and improve the transparency of the glass.

[0024] Step S2, introducing the liquid glass matrix into a forming mold, precooling the liquid glass matrix to make it in a semi-solid state, wherein the depth of the forming mold is 10 mm, that is, the thickness of the prepared explosion-proof glass is 10 mm; The pre-cooling treatment is to cool the liquid glass matrix from a high temperature of 1450-1750°C at a rate of 20-55°C / min to a semi-solid state in the range of 500-750°C, wherein the semi-solid state means that the glass has a certain fluidity but is no longer completely liquid; In this temperature range, the molecules inside the glass material can still move and adjust to a certain extent, but have lost the complete freedom in the liquid state. When directional stress is applied inside the glass matrix later, the Al2O3 nanoparticles can be better evenly distributed in the glass matrix, and precooling the glass to a semi-solid state is not only conducive to forming a uniform compression layer on the glass surface, but also can further optimize the overall stress distribution of the glass, and improve the mechanical properties and impact resistance of the glass. At the same time, the liquid glass matrix is ​​cooled to a temperature of 500-750°C to prepare for the subsequent application of directional stress through an electric field.

[0025] Step S3, applying directional stress to the semi-solid glass matrix to control the symmetrical and uniform distribution of Al2O3 nanoparticles inside the semi-solid glass matrix, and cooling the semi-solid glass matrix to form a solid glass with a compression layer on the surface; Applying directional stress to the semi-solid glass substrate, specifically, applying an electric field to both the upper and lower surfaces of the semi-solid glass substrate, and setting the electric field strength to a range of 10^4-10^6V / m, and applying for 5-10 minutes; Cooling treatment, specifically, after the Al2O3 nanoparticles are arranged, cooling to 23-25°C at a rate of 10-45°C / min to solidify the glass; When directional stress is applied to the semi-solid glass matrix through an electric field, the Al2O3 nanoparticles migrate to both sides of the glass matrix under the action of the electric field. The directional movement enables the nanoparticles to be evenly distributed in the glass matrix and embedded in the network structure, especially concentrated on the surface to form a compression layer, making the structure of the glass compression layer denser, thereby improving the impact resistance and explosion-proof performance of the glass. After the electric field is used to apply directional stress to the semi-solid glass matrix, the semi-solid glass matrix is ​​gradually cooled to a solid state of 23-25°C by cooling the glass, so that its internal structure is stabilized and a uniform compression layer is formed on the surface. At the same time, the position and distribution of the Al2O3 nanoparticles are fixed, and the cooling rate is controlled within the range of 10-45°C / min. Controlling the cooling rate and process can effectively reduce the formation of internal stress in the glass, thereby ensuring uniform cooling of the glass matrix and avoiding the generation of new internal stress, preventing stress concentration caused by uneven cooling, and thus ensuring the transparency and explosion-proof performance of the glass.

[0026] Step S4: performing surface treatment on the formed solid glass, including but not limited to chemical strengthening or physical coating.

[0027] The surface treatment of the formed solid glass includes: chemically strengthening the formed solid glass, immersing the formed solid glass in a potassium nitrate molten bath at a temperature of 400-475°C for 1.25-2 hours, and under high temperature conditions, the smaller Na + ions are replaced by the larger K + Ion substitution, K + Due to their large size, ions will generate compressive stress when embedded in the glass surface, further improving the impact resistance and explosion-proof performance of the glass. After immersion, they are cooled to 23-25°C at a rate of 15-30°C / min. Through slow cooling, the compression layer is stabilized and new internal stress is avoided during the cooling process.

[0028] In summary, by preparing the glass into a hard-soft-hard layered structure, the outer compression layer can withstand and disperse the externally applied stress, thereby reducing the internal stress concentration. The middle soft layer can absorb and disperse the externally applied pressure under the action of stress, thereby slowing down the transfer of stress to the compression layer, reducing the propagation and concentration of stress inside the glass, making the overall stress distribution of the glass more uniform, and reducing the optical distortion and crack generation caused by internal stress.

[0029] In the present invention, in step S11, the modification treatment of Al2O3 nanoparticles includes the following steps: Step S111, selecting Li2O as a modifier, mixing Al2O3 nanoparticles and Li2O for 20-30 minutes to ensure that Li2O is evenly distributed on the surface of the Al2O3 nanoparticles, wherein the mass ratio of Al2O3 nanoparticles to Li2O is 25:1-3; Step S112, heating the uniformly mixed Al2O3 nanoparticles and Li2O to 150-225°C, preheating for 1.5-2h to remove the existing moisture and volatile impurities; Step S113, heating the preheated Al2O3 nanoparticles and Li2O at a high temperature of 850-1000°C for 1.25-2 hours to form a lithium aluminum compound layer covering the surface of the Al2O3 nanoparticles; Step S114, cooling the Al2O3 nanoparticles processed in step S113 to 23-25°C at a speed of 50-100°C / min.

[0030] Because the surface of Al2O3 nanoparticles usually has a strong surface energy, they are easy to agglomerate in the glass matrix, resulting in uneven dispersion, thus affecting the transparency and mechanical properties of the glass. By introducing Li2O as a modifier to modify the Al2O3 nanoparticles, lithium ions can form stable lithium-aluminum compounds with oxygen atoms on the surface of Al2O3 nanoparticles, covering the surface of Al2O3 nanoparticles, reducing the surface energy of Al2O3 nanoparticles and the interaction force between particles, thereby effectively preventing particle agglomeration and improving its dispersibility and reactivity in the glass matrix; at the same time, lithium ions have a smaller ion radius and can penetrate into the glass network, reducing light scattering and further improving the transparency of the glass.

[0031] To explore the effects of different contents of Al2O3 nanoparticles on the transparency, impact strength and internal stress distribution of explosion-proof glass, the following experiments were conducted; Experimental example: 1. Detection method 1. Transmittance detection: Use a spectrophotometer to measure the transmittance of the glass sample in the visible light band (400-700nm). Make the light of the light source incident perpendicular to the glass sample, and measure the ratio of the light intensity passing through the glass to the incident light intensity, which is the transmittance.

[0032] 2. Impact strength test: Use an impact testing machine to test the impact strength. The commonly used method is the "pendulum impact test". The test releases a pendulum to impact the glass sample and measures the energy required to destroy the sample.

[0033] 3. Internal stress distribution detection: Use a photoelastic stress meter (Polarimeter) to detect the stress distribution inside the glass, and evaluate the internal stress by observing the birefringence effect when light passes through the glass.

[0034] 4. Thermal shock resistance test: Use a thermal shock tester to conduct a thermal shock resistance test. Specifically, the glass sample is exposed to high temperature, then quickly cooled, and observed to see if the glass is cracked or broken.

[0035] 5. Surface hardness test: Use Vickers Hardness Tester to measure the surface hardness of the glass. Specifically, use a diamond indenter to press a small dent on the glass surface and measure the diagonal length of the dent to calculate the hardness value.

[0036] 5. Detection of average thickness of compression layer on both sides: Use scanning electron microscope (SEM) or optical microscope to measure the thickness of compression layer on both sides of the glass respectively to obtain the total thickness. Average thickness = total thickness / 2.

[0037] 2. Experimental methods

[0038] Embodiment 1: Select a glass substrate raw material, which is 100 parts by weight of quartz sand, 18 parts of sodium oxide, 13 parts of calcium oxide, 15 parts of boron oxide, 10 parts of potassium carbonate, 5 parts of zinc oxide, and 3 parts of cesium nitrate. Select 1.5 parts by weight of Al2O3 nanoparticles, modify the Al2O3 nanoparticles, and mix and stir with the glass substrate raw material for 20-30 minutes to make the glass substrate raw material and the Al2O3 nanoparticles evenly mixed; The mixed raw materials were dried at 110°C for 2.5 hours, and the dried mixed raw materials were gradually heated to 350-550°C, preheated for 5-10 minutes, and the preheated raw material mixture was gradually heated to 1450-1750°C, maintained for 3 hours to obtain glass liquid, 5 parts by weight of Glauber's salt were added and stirred, and the glass liquid was maintained at a high temperature of 1450-1750°C for 1 hour to obtain a liquid glass matrix; The liquid glass matrix is ​​introduced into a molding mold with a depth of 10 mm, and the liquid glass matrix is ​​cooled to the range of 500-750°C to make it in a semi-solid state. An electric field is applied to both the upper and lower surfaces of the semi-solid glass matrix, and the electric field strength is set to 10^4V / m. The application time is 8 minutes, and the temperature is lowered at a rate of 40°C / min to solidify the glass. The formed solid glass is immersed in a potassium nitrate molten bath at a temperature of 400-475°C for 1.5 hours.

[0039] Example 2: The same as Example 1, except that 2.5 parts by weight of Al2O3 nanoparticles are selected to obtain solid glass; Example 3: The same as Example 1, except that 3.5 parts by weight of Al2O3 nanoparticles are selected to obtain solid glass; Example 4: The same as Example 1, except that 4.5 parts by weight of Al2O3 nanoparticles are selected to obtain solid glass; Example 5: The same as Example 1, except that 5.5 parts by weight of Al2O3 nanoparticles are selected to obtain solid glass; Example 6: The same as Example 4, except that an electric field with an electric field strength of 10^5 V / m is applied to both the upper and lower surfaces of the semi-solid glass substrate to obtain solid glass; Example 7: The same as Example 4, except that an electric field with an electric field strength of 10^6 V / m is applied to both the upper and lower surfaces of the semi-solid glass substrate to obtain solid glass; The glass properties obtained by testing are shown in Table 1.

[0040] Table 1

[0041] By comparing the first to fifth embodiments, it can be concluded that, as the content of Al2O3 nanoparticles gradually increases, the overall performance of the prepared glass is improved, mainly because, as the Al2O3 nanoparticles increase, they react with quartz sand and boron oxide to generate a network structure of aluminum borate and aluminum silicate, which can effectively disperse the externally applied stress and the impact force applied to the glass, thereby avoiding the concentration of stress. Furthermore, through the directional stress applied by the electric field, the Al2O3 nanoparticles are evenly dispersed on both sides of the glass matrix and embedded in the network structure, so that the structure of the compression layer formed by the Al2O3 nanoparticles on the glass surface is more compact, and the protection ability in the face of external force impact is significantly improved, thereby significantly improving the explosion-proof performance and overall performance. Secondly, the addition of Al2O3 nanoparticles effectively reduces bubbles and tiny defects inside the glass, reduces light scattering, and improves light transmittance. In addition, the generated aluminoborate and aluminosilicate network structures further enhance the optical properties of the glass, making the light propagation path more uniform, reducing optical distortion, and thus improving the transparency of the glass. However, as the content of Al2O3 nanoparticles continues to increase, the overall performance of the prepared glass will be reduced. This is mainly because when the content of Al2O3 nanoparticles is too high, the distribution of Al2O3 nanoparticles in the glass matrix may aggregate, and excessive nanoparticles may cause excessive particle concentration in local areas. High-concentration aggregates may form particle agglomeration, forming tiny particle accumulation areas. The accumulation areas will produce stress concentration points, resulting in non-uniform distribution of stress in the glass, which will cause cracks or reduce the overall structural stability of the glass, and have a negative impact on the explosion-proof performance and overall performance; and the increase in the density of Al2O3 nanoparticles will lead to increased light scattering, and the interaction and aggregation effect between Al2O3 nanoparticles will cause light scattering and refraction, thereby reducing the optical clarity of the glass, thereby affecting the light transmittance and reducing the transparency; By comparing Example 4, Example 6, and Example 7, it can be concluded that as the electric field strength increases, the thickness of the obtained glass compression layer becomes larger, and the glass performance can continue to improve. This is mainly because, as the electric field strength increases, the thickness of the compression layer on both sides of the glass also increases, and the Al2O3 nanoparticles can be more evenly distributed in the compression layer, which can more effectively absorb and disperse the impact force applied from the outside, prevent stress concentration and crack propagation, thereby improving the explosion-proof performance. The thicker compression layer also increases the thermal shock resistance of the glass, which can better cope with thermal stress in rapid temperature changes and prevent cracking.

[0042] Al2O3 nanoparticles are more evenly distributed in the compression layer, which can effectively reduce the local stress concentration inside the glass, reduce the optical distortion caused by internal stress, and thus improve transparency and reduce crack generation, which helps the glass to show better durability and stability when facing external impact and thermal stress. At the same time, it reduces light scattering, improves light transmittance, and allows the glass to maintain a high degree of transparency, thereby further improving optical performance; However, as the electric field intensity continues to increase, the thickness of the obtained glass compression layer continues to increase, and the glass performance decreases. This is mainly because the Al2O3 nanoparticle content is insufficient, the impact resistance and stress dispersion ability of the compression layer will be limited, and an overly thick compression layer may cause the internal tensile stress area to increase, resulting in stress concentration and cracks. In addition, if the compression layer is too thick, the Al2O3 nanoparticle content is insufficient, and a sufficient and evenly distributed aluminum borate and aluminum silicate network structure cannot be generated, resulting in increased optical inhomogeneity, affecting the light transmittance and transparency of the glass. At the same time, when the Al2O3 nanoparticle content is insufficient, the gaps and defects in the compression layer cannot be effectively filled, resulting in degradation of optical performance. The glass properties obtained by comparing the preparation method of the present invention with the preparation method of the prior art are compared; Control group: Select glass substrate raw material, which is mixed with 100 parts by weight of quartz sand, 18 parts by weight of sodium oxide, 13 parts by weight of calcium oxide, 15 parts by weight of boron oxide, 10 parts by weight of potassium carbonate, 5 parts by weight of zinc oxide, and 3 parts by weight of cesium nitrate, and select 4.5 parts by weight of Al2O3 nanoparticles, and mix and stir with the glass substrate raw material for 20-30 minutes, so that the glass substrate raw material and the Al2O3 nanoparticles are evenly mixed; The mixed raw materials were dried at 110°C for 2.5 hours, and the dried mixed raw materials were gradually heated to 350-550°C, preheated for 5-10 minutes, and the preheated raw material mixture was gradually heated to 1450-1750°C, maintained for 3 hours to obtain glass liquid, 5 parts by weight of Glauber's salt were added and stirred, and the glass liquid was maintained at a high temperature of 1450-1750°C for 1 hour to obtain a liquid glass matrix; The liquid glass matrix was introduced into a molding mold with a depth of 10 mm, and the liquid glass matrix was cooled at a rate of 40°C / min to solidify the glass. The formed solid glass was immersed in a potassium nitrate molten bath at a temperature of 400-475°C for 1.5 hours, and the properties of the obtained glass were tested, as shown in Table 2.

[0043] Table 2

[0044] By comparing the glass properties obtained in Example 6 and the control group, it can be concluded that the glass properties prepared by the present invention are much higher than those prepared by the prior art. This is mainly because, in the present invention, the directional stress applied by the electric field allows the Al2O3 nanoparticles to be evenly dispersed on both sides of the glass matrix and embedded in the mesh structure, so that the glass is prepared into a hard-soft-hard layered structure, so that the glass on both sides of the glass becomes a more compact compression layer. The compression layer can withstand and disperse the externally applied stress, thereby reducing the internal stress concentration. The middle soft layer can absorb and disperse the externally applied pressure under the action of stress, thereby slowing down the transmission of stress to the compression layer, reducing the propagation and concentration of stress inside the glass, and making the overall stress distribution of the glass more uniform, which not only improves the explosion-proof performance of the glass, but also reduces the explosion-proof performance caused by internal stress. Optical distortion and crack generation; and the compression layer has high rigidity and surface hardness, which can directly bear and disperse the impact force from the outside, thereby avoiding the generation and expansion of cracks. The middle soft layer has good toughness and elasticity, which can effectively absorb and relieve the stress transmitted to the inside through the hard layer. The soft layer will deform when impacted, and the direct impact on the hard layer will be reduced through internal stress transfer and dispersion, which not only reduces stress concentration, but also prevents the expansion of cracks in the hard layer. At the same time, the design of the hard-soft-hard layered structure makes the stress transmission inside the glass more uniform. After the compression layer absorbs the impact, the soft layer disperses the stress by deformation, and finally disperses the remaining stress to another compression layer. This interlayer buffering effect significantly reduces the concentration of internal stress and reduces the risk of glass breakage; Secondly, by introducing Li2O as a modifier to modify the Al2O3 nanoparticles, lithium ions can form stable lithium aluminum compounds with oxygen atoms on the surface of the Al2O3 nanoparticles, covering the surface of the Al2O3 nanoparticles, reducing the surface energy of the Al2O3 nanoparticles, reducing the interaction force between the particles, thereby effectively preventing particle agglomeration and improving its dispersibility and reactivity in the glass matrix; at the same time, lithium ions have a smaller ion radius and can penetrate into the glass network, reducing light scattering and further improving the transparency of the glass; in summary, Example 6 is the optimal solution.

[0045] A highly transparent explosion-proof glass is prepared according to any one of the preparation processes for a highly transparent explosion-proof glass.

[0046] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A process for preparing highly transparent explosion-proof glass, characterized in that: The following steps are involved: Step S1, mixing quartz sand, sodium oxide, calcium oxide, boron oxide, potassium carbonate, sodium sulfate, zinc oxide, cesium nitrate, and Al2O3 nanoparticles in proportion and heating until they are molten to obtain a liquid glass matrix; Step S2, introducing the liquid glass matrix into a forming mold, and precooling the liquid glass matrix to make it in a semi-solid state; Step S3, applying directional stress to the semi-solid glass matrix to control the symmetrical and uniform distribution of Al2O3 nanoparticles inside the semi-solid glass matrix, and cooling the semi-solid glass matrix to obtain a compression layer, so that the glass has a hard-soft-hard layered structure; Step S4: performing surface treatment on the formed solid glass, including but not limited to chemical strengthening or physical coating.

2. The process for preparing a highly transparent explosion-proof glass according to claim 1, characterized in that: In the step S1, the following sub-steps are included: Step S11, selecting a glass substrate raw material, mixing 100 parts by weight of quartz sand, 15-20 parts by weight of sodium oxide, 10-15 parts by weight of calcium oxide, 6-18 parts by weight of boron oxide, 5-12 parts by weight of potassium carbonate, 3-7 parts by weight of zinc oxide, and 1-5 parts by weight of cesium nitrate, selecting 1.5-5.5 parts by weight of Al2O3 nanoparticles, modifying the Al2O3 nanoparticles, and mixing with the glass substrate raw material for 20-30 minutes; Step S12, drying the mixed raw materials at 110° C. for 2-3.5 hours to remove moisture from the mixed raw materials, and gradually heating the dried mixed raw materials to 350-550° C. for preheating; Step S13, gradually heating the preheated raw material mixture to 1450-1750° C. and maintaining the temperature for 2.5-6 hours until the raw material mixture is fully melted and forms a uniform glass liquid; Step S14: After melting is completed, 2-8 parts by weight of Glauber's salt is added and stirred, and the glass liquid is maintained at a high temperature of 1450-1750° C. for 0.5-2 hours to ensure thorough clarification and achieve uniform chemical composition, thereby obtaining a liquid glass matrix.

3. The process for preparing a highly transparent explosion-proof glass according to claim 2, characterized in that: In the step S11, the modification treatment of Al2O3 nanoparticles includes the following steps: Step S111, selecting Li2O as a modifier, mixing Al2O3 nanoparticles and Li2O for 20-30 minutes to ensure that Li2O is evenly distributed on the surface of the Al2O3 nanoparticles; Step S112, heating the uniformly mixed Al2O3 nanoparticles and Li2O to 150-225°C, preheating for 1.5-2h to remove the existing moisture and volatile impurities; Step S113, heating the preheated Al2O3 nanoparticles and Li2O at a high temperature of 850-1000°C for 1.25-2 hours to form a lithium aluminum compound layer covering the surface of the Al2O3 nanoparticles; Step S114, cooling the Al2O3 nanoparticles processed in step S113 to 23-25°C at a speed of 50-100°C / min.

4. The process for preparing a highly transparent explosion-proof glass according to claim 3, characterized in that: The mass ratio of the Al2O3 nanoparticles to Li2O is 25:1-3.

5. The process for preparing a highly transparent explosion-proof glass according to claim 1, characterized in that: In step S2, the pre-cooling treatment is specifically to cool the liquid glass matrix to a semi-solid state in the range of 500-750°C, at which time the glass has a certain fluidity but is no longer completely liquid.

6. The process for preparing a highly transparent explosion-proof glass according to claim 1, characterized in that: In the step S3, directional stress is applied to the semi-solid glass substrate. Specifically, an electric field is applied to both the upper and lower surfaces of the semi-solid glass substrate, and the electric field strength is set to a range of 10^4-10^6 V / m, and the application time is 5-10 min.

7. A process for preparing a highly transparent explosion-proof glass according to claim 1, characterized in that: In step S3, the temperature is lowered, specifically, after the Al2O3 nanoparticles are arranged, the temperature is lowered at a rate of 10-45°C / min to solidify the glass.

8. The process for preparing a highly transparent explosion-proof glass according to claim 1, characterized in that: In step S4, surface treatment of the formed solid glass includes: The formed solid glass is subjected to chemical strengthening treatment by immersing the formed solid glass in a potassium nitrate molten bath at a temperature of 400-475° C. for 1.25-2 hours. After the immersion is completed, the solid glass is cooled to 23-25° C. at a rate of 15-30° C. / min.

9. A highly transparent explosion-proof glass, characterized in that: The glass is prepared based on the preparation process of a highly transparent explosion-proof glass according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite reinforcing method of high-alkali aluminosilicate glass

    CN112358198A

  • Lithium-aluminum-silicon polarizing glass as well as preparation method and application thereof

    CN115403270A

  • Composition for preparing high-aluminum glass, high-aluminum glass as well as preparation method and application of high-aluminum glass

    CN116903248A

  • Ultra-white double-tempered glass and processing technology thereof

    CN118993529A

Cited By

  • Preparation method of anti-burst glass

    CN120080618A

  • A method for preparing explosion-proof glass

    CN120080618B

  • Fireproof and explosion-proof glass with high acid and alkali resistance and preparation method thereof

    CN122627665A